Caracterización de la función luteal durante el primer ciclo post-parto inducido por medio de un progestágeno en vacas cebú brahman en amamantamiento (1997)
ABSTRACT: Nineteen Brahman breed under sucled cows were studied. They reached 3-5 months post-partum, and were selected to determinate the time period of luteal stage and the production patterns of P4 during the first post-partum cycle, in order to established the kind of luteal deficiency related with low pregnancy rates. The induced group (n = 12) received Norgestomet subcutaneously (6 mg) and intramuscularly (3 mg). and estradiol valerato (5 mg). the implant (subcutaneous) was removed ten days later. The 91.6% of the induced cows showed estrous between 36-48 h after the remotion of the implant (against 42.85% of control cows during 2 months under the observation). The pregnancy rate obtained after the artificial insemination (A.I) during this first induced estrous was 9%. Eight of 11 (66%) induced animal with estrous (72.7%) showed luteal activity. Of these, 75% showed corpus leteum a mean life (> 14 days). Cows with lower values of P4 have more relation with a "delay" in their secretory capacity during the cicle's first days, that with early corpus luteum lisis. That "delay" is just overcome by the day tenth of the cycle and couses the short time period of the corresponding luteal stage.